2017
DOI: 10.7567/jjap.56.07jf18
|View full text |Cite
|
Sign up to set email alerts
|

Mutual conversion between B-mode image and acoustic impedance image

Abstract: To study the acoustic properties of a B-mode image, two ways of analysis methods were proposed in this report. The first method is the conversion of an acoustic impedance image into a B-mode image (Z to B). The time domain reflectometry theory and transmission line model were used as reference in the calculation. The second method is the direct a conversion of B-mode image into an acoustic impedance image (B to Z). The theoretical background of the second method is similar to that of the first method; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In our previous report, we showed that cell elasticity contributes to the major changes in the acoustic impedance value, as SAM mapped the cells by interpreting the reflection signals coming from the cytoskeleton. 5,7,8,11,12,30,31) While conventional optical microscopy also provides us with information on the cell morphology, SAM was able to provide us with the changes of the acoustic impedance value of cells upon drug treatment, which is infeasible in optical microscopy. 6,9,10,13) This indicates that SAM has the potential to provide more information in cell study as compared to optical microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous report, we showed that cell elasticity contributes to the major changes in the acoustic impedance value, as SAM mapped the cells by interpreting the reflection signals coming from the cytoskeleton. 5,7,8,11,12,30,31) While conventional optical microscopy also provides us with information on the cell morphology, SAM was able to provide us with the changes of the acoustic impedance value of cells upon drug treatment, which is infeasible in optical microscopy. 6,9,10,13) This indicates that SAM has the potential to provide more information in cell study as compared to optical microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…During the conversion into an acoustic impedance profile, 8,9,21,22) the tissue is divided along its depth into many fragments; the thickness of each corresponds to the round-trip time within the sampling interval. In this series of analyses, the speed of sound is assumed to be 1600 m s −1 .…”
Section: System Setupmentioning
confidence: 99%
“…This level of threshold determines how much of the low-frequency component is included in the calculation and strongly affects the quality of the image when converting it into an acoustic impedance distribution. Since the acoustic impedance conversion utilizes an algorithm similar to that used in time-domain reflectometry (TDR), 9,21,22) which works by integrating each segment in a signal, a small drift in the signal caused by a disturbed low-frequency component leads to an error in integration and forms a strong artifact with high acoustic impedance in the image.…”
Section: System Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Skin elasticity was evaluated by measuring Ur/Uf 3 times with a Cutometer. The thickness of the papillary dermis at the cheek was evaluated by scanning acoustic microscopy, as described 42 .…”
Section: Clinical Studymentioning
confidence: 99%